Application of MBSAP to a Complex Problem with Social Dimensions: Utilization in Outpatient Imaging Centers. Issue 3 (6th October 2021) - Speece, Jill; Shahroudi, Kamran Eftekhari
ABSTRACT: Outpatient imaging centers struggle daily to manage the negative impact of same day missed appointments. The technical component of outpatient imaging centers includes a complex IT infrastructure and advanced medical imaging equipment. The social component of outpatient imaging centers includes stakeholders that regularly interact with these technologies and one another all to help physicians diagnose their patients. The effectiveness of the technology used in outpatient imaging is dependent on operator ability and stakeholder collaboration. Problems in this type of system require intentional systems thinking to understand stakeholder needs. The Model‐Based System Architecture Process (MBSAP) provides a visually understandable framework for system development in an industry unfamiliar with Systems Engineering methods. The primary social dimensions in outpatient imaging are the Customer Dimension, Planning Dimension, Operations Dimension, and Technical Dimension. Each dimension has stakeholders with a diverse set of needs that must be well‐understood and incorporated into the requirements. This paper presents an architecture for a system that utilizes all available exam time slots without a dependency on modifying patient behavior to prevent same day missed appointments. The MBSAP artefacts are the starting point for making the system a reality with stakeholders and finding the right balance between separate social dimensional measures.